SUSTAINABILITY ISSUES IN FINANCIAL ACCOUNTING RESEARCH - Muhammad Putra Aprullah; Raida Fuadi; Indrayani Indrayani; Zahara Zahara; Agus Adria; Muhammad Sayuthi; Salsabilla Julnadi; William Ben Gunawan (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT In financial accounting, sustainability is predominantly analyzed through corporate social responsibility (CSR) and environmental, social, and governance (ESG) frameworks, both of which are now integral to economic decision-making. Sustainability has become a central concern in global business and investment. The purpose of this essay is to review the literature on sustainability issues in financial accounting, with particular emphasis on information related to ESG practices. This study employs a literature review, analyzing journal articles to synthesize key findings and identify prevailing patterns. ESG research in financial accounting predominantly examines implications for financial performance, firm value, and capital costs from the perspectives of investors and creditors. While long-term benefits are acknowledged, concerns persist that ESG may obscure accounting malpractices, such as earnings management, which can erode its credibility with stakeholders. This study is not deeply explaining about behavioural factors, fraudulent practices, and creative accounting in the relationship between ESG practices and accounting variables. This study views comprehensively to prevent fraudulent accounting practices, such as earnings management and fraud. Therefore, the role of internal control systems and public auditors must be to ensure the reliability of the company's ESG information, as more and more investors, creditors, and other stakeholders use ESG information in assessing the company's business prospects and risks. This essay provides a timely synthesis that highlights the ESG paradox in financial accounting, contrasting its value as a sustainability indicator with its potential to enable opportunistic behavior. The analysis emphasizes the urgent need for regulatory intervention. ABSTRAK Dalam akuntansi keuangan, keberlanjutan sebagian besar dianalisis melalui tanggung jawab sosial perusahaan (CSR) dan kerangka kerja lingkungan, sosial, dan tata kelola (ESG), yang keduanya kini menjadi bagian integral dari pengambilan keputusan ekonomi. Keberlanjutan telah menjadi perhatian utama dalam bisnis dan investasi global. Tujuan esai ini adalah untuk meninjau literatur tentang isu-isu keberlanjutan dalam akuntansi keuangan, dengan penekanan khusus pada informasi yang berkaitan dengan praktik ESG. Studi ini menggunakan tinjauan literatur, menganalisis artikel jurnal untuk mensintesis temuan utama dan mengidentifikasi pola yang berlaku. Penelitian ESG dalam akuntansi keuangan sebagian besar mengkaji implikasi terhadap kinerja keuangan, nilai perusahaan, dan biaya modal dari perspektif investor dan kreditor. Meskipun manfaat jangka panjang diakui, kekhawatiran tetap ada bahwa ESG dapat mengaburkan praktik akuntansi yang salah, seperti manajemen laba, yang dapat mengikis kredibilitasnya di mata pemangku kepentingan. Studi ini tidak menjelaskan secara mendalam tentang faktor perilaku, praktik curang, dan akuntansi kreatif dalam hubungan antara praktik ESG dan variabel akuntansi. Studi ini melihat secara komprehensif untuk mencegah praktik akuntansi curang, seperti manajemen laba dan kecurangan. Oleh karena itu, peran sistem pengendalian internal dan auditor publik harus memastikan keandalan informasi ESG perusahaan, karena semakin banyak investor, kreditor, dan pemangku kepentingan lainnya menggunakan informasi ESG dalam menilai prospek bisnis dan risiko perusahaan. Esai ini memberikan sintesis tepat waktu yang menyoroti paradoks ESG dalam akuntansi keuangan, membandingkan nilainya sebagai indikator keberlanjutan dengan potensinya untuk memungkinkan perilaku oportunistik. Analisis ini menekankan kebutuhan mendesak akan intervensi regulasi.